Exports and economic growth in South Africa - Feddersen, Maura (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2014)
Various studies conclude that accelerated economic growth and development are necessary in South Africa to make a significant contribution towards reducing high levels of unemployment, inequality and poverty. Moreover, in theories of economic growth the export sector is frequently accorded a special role in encouraging faster economic growth, which is often supported by empirical evidence. Nonetheless, a question that remains unresolved is whether higher export growth leads to higher economic growth in South Africa and what particular role exports may play within the overall economic growth process of the country. This study applies Johansen's cointegration procedure, impulse response functions, variance decomposition analysis and Granger causality tests to shed light on the channels through which export growth may impact South Africa's economic growth rate. Quarterly time series data ranging from 1975q1 to 2012q4 is employed in the study's empirical tests. The empirical results lend support to the idea that the role of exports in the economic growth process fundamentally lies in their ability to encourage investment and capital formation. While export growth supports higher economic growth in the short-run, it does not have the same effect in the long-run. Nonetheless, with export growth supporting faster capital formation in South Africa, and capital formation, in turn, significantly increasing economic growth in the long-run, the impetus to growth stemming from exports has been found to lie in the channel to capital formation. On the basis of the empirical results, not only are exports a critical requirement of higher investment, but they are also anticipated to play a prominent role in lifting the balance of payments constraint that would make investment-led growth possible in the first place. Overall, a strategy of export-led growth that does not explicitly emphasise the export-capital-growth connection is likely to fall short of reflecting the dynamics contained within the exports-growth relationship in South Africa.
Keywords: Exports -- South Africa; Economic development -- South Africa; Unemployment -- South Africa; Poverty -- South Africa; Income distribution -- South Africa; Investments -- South Africa; Saving and investment -- South Africa; South Africa -- Economic conditions; South Africa -- Social conditions